MILKING EQUIPMENT VACUUM PUMPS AND THEIR IMPACT ON ENVIRONMENT (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
The aim of the research was to compare different milking equipment vacuum pumps purchased in Latvia according to their influence on the environment and profitability. Information on vacuum pumps available in Latvia is summarised and their classification is elaborated in the investigation. The amount of the working liquid discharged from the vacuum pumps during their operation is experimentally determined. It is stated that for the new lubricated vacuum pumps with oil recirculation system and the pumps with the oil screen the discharge of oil is reduced 60-199 times and it does not essentially influence the environment. The vacuum pumps with lead in their blades produced in Rezekne are also experimentally investigated. It is stated that they are sufficiently wear resistant and they are suitable for operation in mobile milking machines. Vacuum pumps with capacity 800-1000 l/min are compared according to their operational costs. It is stated that the water ring type vacuum pumps produced in Estonia have the lowest costs but the lubricated vacuum pump UVU 45/60 produced in Russian has the highest costs.